The complete mitochondrial genome of Ochotona sacraria (Lagomorpha: Ochotonidae). Issue 2 (2nd April 2020) - Li, Feng-Jun; Wang, Xu-Ming; Jiang, Hai-Jun; Wang, Qiong; Chen, Shun-de
Abstract: A pika species Ochotona thibetana sacraria (Lagomorpha) (Thomas 1923 ), was reported as a subspecies of O. thibetana . To date, this subspecies have been elevated to species status . O. sacraria belongs to a new subgenus Alienauroa and is endemic to Mount Emei of Sichuan, China. In this study, the complete mitogenome of O. sacraria was determined. The mitogenome is a circular molecule of 16, 573 bp in length, containing 13 protein-coding genes, 2 ribosome RNA genes, 1 light strand replication origin (OL), 22 transfer RNA genes and 1 non-coding region. We reconstructed a phylogenetic tree based on Bayesian inference for 12 small mammal species. The new mitogenome data would provide useful information for application in conservation genetics and further clarify phylogenetic evolution of this species.